Late entry into HIV care: lessons from Brazil, 2003 to 2006 - Grangeiro, Alexandre (BioMed Central, 2012)
BACKGROUND: To ascertain the population rates and proportion of late entry into HIV care, as well as to determine whether such late entry correlates with individual and contextual factors. METHODS: Data for the 2003–2006 period in Brazil were obtained from public health records. A case of late entry into HIV care was defined as one in which HIV infection was diagnosed at death, one in which HIV infection was diagnosed after the condition of the patient had already been aggravated by AIDS-related diseases, or one in which the CD4(+) T-cell count was ≤ 200 cells/mm(3) at the time of diagnosis. We also considered extended and stricter sets of criteria (in which the final criterion was ≤ 350 cells/mm(3) and ≤ 100 cells/mm(3), respectively). The estimated risk ratio was used in assessing the effects of correlates, and the population rates (per 100,000 population) were calculated on an annual basis. RESULTS: Records of 115,369 HIV-infected adults were retrieved, and 43.6% (50,358) met the standard criteria for late entry into care. Diagnosis at death accounted for 29% (14,457) of these cases. Late entry into HIV care (standard criterion) was associated with certain individual factors (sex, age, and transmission category) and contextual factors (region with less economic development/increasing incidence of AIDS, lower local HIV testing rate, and smaller municipal population). Use of the extended criteria increased the proportion of late entry by 34% but did not substantially alter the correlations analyzed. The overall population rate of late entry was 9.9/100,000 population, specific rates being highest for individuals in the 30–59 year age bracket, for men, and for individuals living in regions with greater economic development/higher HIV testing rates, collectively accounting for more than half of the cases observed. CONCLUSIONS: Although the high proportion of late entry might contribute to spreading the AIDS epidemic in less developed regions, most cases occurred in large cities, with broader availability of HIV testing, and in economically developed regions.